0056 Abnormal Clock Gene Oscillation And Decreased Sirt1 Expression Causes Abnormal Circadian Rhythms In Epileptic Kv1.1 Knock Out Mice. (27th April 2018) - Maganti, R; Wallace, E; Williams, J3; Wright, S
Abstract: Introduction: Circadian rhythms are known to be abnormal in many neurological disorders. While sleep disturbances are known in epilepsy, data on circadian rhythm disturbances in epilepsy are sparse. Here we examined circadian rest-activity and sleep-wake patterns in Kcna1 -null mice, a genetic model of epilepsy. We then explored to evaluate whether seizures or aberrant oscillation of core Clock genes and an epigenetic regulator, Sirtuin 1 are associated with disrupted rest-activity rhythms. Methods: We used infrared actigraphy to assess circadian rest-activity patterns, electroencephalography for seizure and sleep analysis and molecular techniques (RT-PCR and Western Blot) to evaluate clock gene and Sirt1 expression patterns in Kcna1 -null and wild-type mice. Results: Epileptic Kcna1 -null animals have drastically disrupted diurnal and circadian rest-activity patterns as well as a prolonged circadian period. Electroencephalographic analysis showed that epileptic mice spend more time in awake and less time in NREM and REM vigilance states. In addition, sleep and wake bout characteristics of Kcna1 -null mice are significantly altered compared to wild-type littermates, regardless of lighting conditions. We found that several core Clock genes (i.e., clock, bmal1, per1 and per2 ) that regulate circadian rhythms had attenuated amplitude of oscillations in the anterior hypothalamic region independent of lighting conditions. Moreover, the epigenetic regulator of clock genes namely Sirt1, a histone deacytelase had reduced expression in hypothalamus of Kv1.1-/- mice. However, we found no correlation between daily seizure counts and the degree of sleep disruption in this model. Conclusion: Aberrant oscillation of several core Clock genes and decreased Sirt1 expression, may underlie the aberrant circadian rhythms observed in Kcna 1-null mice. Sirtuins may represent useful therapeutic targets for rescuing clock gene circadian rhythmicity and sleep patterns in epilepsy. Support (If Any): UW Medical Foundation; Arizona Biomedical Research Foundation